Sulphate reduction utilizing hydrolysis of complex carbon sources - Molipane, Ntaoleng Patricia (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1999)
Due to environmental pollution caused by acid mine drainage (AMD), the Department of Water Affairs has developed a National Water Bill for managing and controlling the water environment to prevent AMD pollution. The application of sulphate reducing bacteria have been demonstrated for the treatment of AMD. However, the scale-up application of this technology ultimately depends on the cost and availability of a carbon source. This study evaluated the use of sewage sludge to provide a carbon source for sulphate reduction in synthetic drainage wastewaters. The demonstration of this process in a laboratory-scale reactor proved that sewage sludge could provide a useful model and viable carbon source for evaluation of sulphate reduction as a process for treating AMD. Since sewage sludge is a complex carbon source, hydrolysis reactions controlling the anaerobic digestion of particulate substrate from this medium were optimized by evaluating the effect of pH on hydrolysis. Controlled and uncontrolled pH studies were conducted using a three stage mixed anaerobic reactor. Analysis of the degradation behaviour of the three important organic classes (carbohydrate, proteins and lipids) revealed that each class followed an indvidual trend with respect to pH changes. In addition, the solubilization of organic particulate carbon was also shown to be a function of pH. The hydrolysis pattern of organic substrate and COD solublization was induced at pH 6.5 rather than at high pH values (7.5 and 8.5). The biodegradation activity of sewage sludge was characterized by the API-ZYM1N test system to provide rapid semiquantitative information on the activity of hydrolytic enzymes associated with the degradation of carbohydrates, lipids, proteins and nucleic acids. A wide range of enzyme activities with phosphatases, aminopeptidases, and glucosyl hydralases dominating were displayed. The pattern of substrate hydrolysis correlated to the degradation efficiency of each organic class as a function of pH. The evaluation of scale-up application for sulphate reduction utilizing sewage sludge as a carbon source demonstrated that large water volume flows could possibly be treated with this cost-effective technology. Generation of alkalinity and sulphide in this medium was shown to be successful in the removal of heavy metals by precipitation. The use of this technology coupled to reduced cost involved showed that biological sulphate reduction utilizing hydrolysates of complex organic particulate from sewage sludge ss a carbon source has a potential scale-up application for the treatment of AMD.
Keywords: Sewage sludge; Acid mine drainage; Hydrolysis